Implementasi Peran Guru Fikih dalam Menumbuhkan Kreativitas Belajar Siswa Madrasah Salafiyah Ula Nashrus Sunnah Madiun - Ariyanti; Widya Nirmala; Nurisma Salsabila Zahra; Devi Triana; Amelia Puspita; Anin Rohman Nita (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2025)
Creativity is a fundamental aspect of modern education, yet its integration into religious subjects like Fiqh often faces unique pedagogical challenges. This study aims to analyze the role of Fiqh teachers in developing the learning creativity of sixth-grade students at Madrasah Salafiyah Ula (MSU) Nashrus Sunnah in Madiun. To achieve this objective, a descriptive qualitative approach was employed, utilizing data collection techniques such as in-depth interviews, direct observations, and documentation analysis of instructional activities. The results of the study indicate that Fiqh teachers perform multifaceted roles as motivators, inspirers, and guides throughout the learning process. By implementing interactive methods including Fiqh-based case discussions, project-based learning, and the use of creative visual media teachers successfully encouraged students to think critically and innovatively about religious jurisprudence. The findings reveal that supporting factors for this development include a conducive madrasah environment and strong collaboration between teachers and parents. However, significant obstacles such as limited facilities, infrastructure constraints, and restricted instructional time remain challenges that must be addressed. Based on these findings, this study provides recommendations for Fiqh teachers to continuously enhance their pedagogical competence and adopt more varied, student-centered approaches. Furthermore, the study suggests that madrasah administrators should prioritize infrastructure development to fully maximize students’ creative potential in religious education.